A French for the Algerian city: : What do young people think ? - HEDID, Souheila (Journal of Human Sciences, 2022)
In this work, we try to take stock of the sociolinguistic situation in Algerian cities, emphasizing the survey methodologies used to identify the place of French in Algerian urban multilingualism (U. Hannerz, 1983) . The research is based on a field survey in the city of Constantine and on a heterogeneous corpus. Our study will try to answer the following questions: What is the place of French in Algerian urban multilingualism? What methodology should be adopted to address the issue with young Algerians today? The work carried out in this direction is generally based on field surveys where the investigator observes or surveys one or more groups in a well-defined context. In this research, we try to survey the same group in several socio-discursive contexts to better observe linguistic changes among informants (P. Lamarre 2009).